Enhancing Future Health Equity Plans: Insights from an Evaluation of Public Health Equity Resources in Oregon - Alyssa Pinoliar; Genevieve Ellis; Marie Boman-Davis; Erika Westling (Mary Ann Liebert, 2024)
Health Equity Action Plans (HEAPs) are a recent strategy employed across health and human services to promote health equity. To inform the development of future HEAPs, as well as to build upon previous initiatives, we evaluated 52 health equity plans and resources from Oregon counties using five criteria: creation date, process orientation, racial equity lens, metrics, and community engagement. When developing future HEAPs, we recommend explicit commitments to collaborate with marginalized communities, to establish measurable goals and defined metrics for assessing progress, to include voices and perspectives of those affected by health inequities, and to detail community strengths, assets, and resources.